2019
DOI: 10.1002/mawe.201900036
|View full text |Cite
|
Sign up to set email alerts
|

Simulation‐aided development of a robust thermoclinching joining process for hybrid structures with textile reinforced thermoplastic composites and metallic components

Abstract: In order to take advantage of the specific structural and functional properties inside a multi-material assembly, it is necessary to provide adapted joining technologies. Therefore, the new joining technology "thermoclinching" was developed to join endless fiber reinforced thermoplastic composites and metallic joining partners. Previous experimental and numerical studies demonstrated the potential of the novel joining technology. In experimental and numerical studies essential geometrical and material paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…As both sheets have a local preparation, high positioning accuracies of the sheets to each other are required ( Table 4 ). For this reason, Thermoclinching was improved regarding a robust and reproducible joining process [ 32 ]. Thereby, the cutting, heating, and joining processes are combined in an inline-Thermoclinching process to increase the process capability and reduce cycle times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As both sheets have a local preparation, high positioning accuracies of the sheets to each other are required ( Table 4 ). For this reason, Thermoclinching was improved regarding a robust and reproducible joining process [ 32 ]. Thereby, the cutting, heating, and joining processes are combined in an inline-Thermoclinching process to increase the process capability and reduce cycle times.…”
Section: Discussionmentioning
confidence: 99%
“…The studies show that a stepwise CT analysis serves as an adequate method to identify and describe the principle deformation characteristics during the Thermoclinching process. Furthermore it was observed that the deformation characteristics, and therefore the joint quality, is significantly dependent on a wide range of parameters such as tool geometry and joint dimensions, as well as material of the joining partners and process parameters [ 32 ].…”
Section: Process Phenomenamentioning
confidence: 99%
“…Based on this technology, hole-clinching [7][8][9], shear-clinching [10][11][12][13][14][15][16], friction-stir clinching [17][18][19][20][21], clinching-welding technology [22][23][24], and clinch-bond composite technology [25,26] have been developed and applied. The materials have been extended from carbon steel and aluminum alloy to new types of refractory materials such as high-strength steel [27][28][29][30][31][32][33], titanium alloy, and magnesium alloy, which present special advantages in the connection between a metal and a non-metal (carbon fiber and polymer [34][35][36][37][38][39][40][41][42][43][44][45][46]). The technology of connecting the double layers of the same or different materials has become mature, and the research on three layers and above is making progress.…”
Section: They Installed Industrial Robots With Clinching Devices Tomentioning
confidence: 99%
“…However, detailed information about the resultant material structure are not available. Another modelling approach on mesoscale for a novel hybrid thermoclinch joining process [9] is shown in [10]. The fabric was modelled in detail with each roving, which is assumed to follow an elasto-plastic material behaviour.…”
Section: /2mentioning
confidence: 99%